Vocal flexibility in nonhuman primates and the origins of human language - Hélène Bouchet; Hiroki Koda; Nobuo Masataka; Alban Lemasson (Revue de Primatologie)
Nobuo Masataka (University of Kyoto, Japan), Alban Lemasson (University of Rennes 1, France) and their colleagues have been collaborating for over a decade on projects investigating nonhuman primates' vocal behaviour and tackling the issue of the evolutionary origins of human language. They have worked together on topics including vocal flexibility under social influences in adults, the development of communicative abilities during ontogeny, and auditory and visual perception of social and non-social stimuli. In this paper, we review this work within the theoretical framework of language evolution.